1997
DOI: 10.1126/science.277.5334.1996
|View full text |Cite
|
Sign up to set email alerts
|

Human DNA-(Cytosine-5) Methyltransferase-PCNA Complex as a Target for p21 WAF1

Abstract: DNA-(cytosine-5) methyltransferase (MCMT) methylates newly replicated mammalian DNA, but the factors regulating this activity are unknown. Here, MCMT is shown to bind proliferating cell nuclear antigen (PCNA), an auxiliary factor for DNA replication and repair. Binding of PCNA requires amino acids 163 to 174 of MCMT, occurs in intact cells at foci of newly replicated DNA, and does not alter MCMT activity. A peptide derived from the cell cycle regulator p21(WAF1) can disrupt the MCMT-PCNA interaction, which sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
589
3
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 852 publications
(623 citation statements)
references
References 34 publications
17
589
3
3
Order By: Relevance
“…DNMT1 is also recruited to nascent DNA by the essential cofactor UHRF1 (ubiquitin-like, with PHD and RING finger domains 1), which exhibits a high affinity for hemi-methylated DNA through its SRA domain 8,9 and ubiquitinates the histone H3 tail to facilitate DNMT1 recruitment 10 . DNMT1 activity is further directed to the replication fork through its interaction with the proliferating cell nuclear antigen (PCNA) DNA clamp 11 , and deletion of DNMT1s PCNA-binding domain has been reported to delay post replication remethylation 12 . More conceptually, accurate reestablishment of the human methylome requires catalytic activity at ~45 million heterogeneously distributed CpGs (roughly 80% of CpG sites within the diploid genome) that must be completed within a single cell cycle 13 .…”
Section: Introductionmentioning
confidence: 99%
“…DNMT1 is also recruited to nascent DNA by the essential cofactor UHRF1 (ubiquitin-like, with PHD and RING finger domains 1), which exhibits a high affinity for hemi-methylated DNA through its SRA domain 8,9 and ubiquitinates the histone H3 tail to facilitate DNMT1 recruitment 10 . DNMT1 activity is further directed to the replication fork through its interaction with the proliferating cell nuclear antigen (PCNA) DNA clamp 11 , and deletion of DNMT1s PCNA-binding domain has been reported to delay post replication remethylation 12 . More conceptually, accurate reestablishment of the human methylome requires catalytic activity at ~45 million heterogeneously distributed CpGs (roughly 80% of CpG sites within the diploid genome) that must be completed within a single cell cycle 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The cell cycle inhibitor p21 CIP1 can disrupt the association between DMT and PCNA, perhaps a ecting the activity of the two proteins (Chuang et al, 1997). Furthermore, levels of DMT and p21 proteins were inversely related in normal and SV-40 transformed human ®broblasts.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, PCNA expression did not vary greatly among the cell lines, and was not signi®cantly correlated with DMT expression. It has been suggested (Chuang et al, 1997) that the transforming e ect of DMT overexpression observed by others (Wu et al, 1993) may be due in part to the ability of DMT to compete with p21 for PCNA binding, thereby promoting the G 1 -S phase transition. By binding to PCNA in place of p21, excess DMT could increase the level of active cyclin-dependent kinases, promoting Rb phosphorylation and thus progression through the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…p21 has several cellular binding partners, including GADD45 damage response protein (Kearsey et al, 1995) and PCNA (Chen et al, 1995). The sequestration of PCNA by p21 from the replication machinery proteins inhibits DNA replication (Flores-Rozas et al, 1994) and interferes with the interaction of PCNA with DNA methyltransferases (Chuang et al, 1997). The loss of p21 leads to defective damage responses and loss of G 1 and mitotic checkpoint control (Brugarolas et al, 1995;Deng et al, 1995).…”
Section: Introductionmentioning
confidence: 99%